Genealogi Larangan Sasuku: Menelusuri Akar Fikih dan Filosofi Adat dalam Perkawinan Minangkabau - Junidar Sartika; Asfar Hamidi Siregar (PT PUSTAKA CENDEKIA GROUP, 2025)
This research is motivated by the existence of Minangkabau customs which have a tradition of prohibiting marriage within the same tribe. This means that in Minangkabau customs it is forbidden for a man to have the same tribe as a woman he wants to marry. Interestingly, there is no verse in the Qur'an or Hadith regarding this marriage within the same tribe, while Minangkabau customs adhere to the principle commonly known by its proverb, namely